Resilience to unusual flooding after 2021 tropical storms in part of mainland Southeast Asia - Wattanachareekul, Pawat; Choowong, Nutcha; Pailoplee, Santi; Choowong, Montri (Frontiers in Ecology and Evolution, 2023)
In Southeast Asian countries, flooding is common and occurs a few weeks after tropical storms. In Thailand, the government’s approach to dealing with flooding is focused on the construction of anthropogenic megastructures. The loss of life, property, and ecosystem from flooding still occurs and will likely become increasingly more severe soon due to global climate variation. Here, in this brief report, we show a case study analyzing the cause of unusual flooding that occurred from September to November 2021 during the tropical depression “Dianmu” and the tropical cyclone “Kompasu” that hit the Khorat Plateau, northeastern Thailand. These two tropical storms left behind vast flooded urban and agricultural areas in the upstream part of the Chi River on this, the largest plateau in mainland Southeast Asia. The flood water stagnated for a month and unusually drained downslope in the upstream zone. In this work, a series of free online access satellite images taken by the Sentinel-1 C band GRD and Sentinel-2 available in the Google Earth engine platform was analyzed. As a result, we confirmed that the normal nature of water flow was problematic due to the presence of anthropogenic structures, especially roads. The installation of different design and dimensions of culverts are urgently recommended, particularly in the floodplain zone. The quick responsible idea provided in this paper highlights and simplifies the resilience to future extreme weather events of the rural community and ecosystem.